Factores que influyen en la utilización de los plaguicidas y las alteraciones en la salud de los agricultores de las comunidades rurales de la parroquia Lucero. - Palma Castillo, Yohana Lucía. (2015)
In the locality of El Lucero, which belongs to the Calvas Canton in the Province of Loja, a study was conducted on “Factors influencing the use of pesticides and changes in the health of the farmers in the rural communities of the Lucero parish”. This work aimed: To determine the socio-cultural factors that influence the farmers to use pesticides on crops and the subsequent changes in health. It was a cross- sectional, the sample was selected via the simple random method in which 167 people participated, of which 146 used pesticides on their crops. For farmers in this area, the land is impoverished and does not have the necessary nutrients for good quality production. In 52% of the participants, the forms of exposure were related to inadequate practices of biosafety. The main problems presented by the use of pesticides were: headaches, lack of motivation, changes in character and sleep disturbances, among others. Key words: farmer, pesticides, changes, health